Development of an assessment tool for mathematical reading, analytical thinking and mathematical writing - Nuttida Kesorn; Putcharee Junpeng; Metta Marwiang; Kissadapan Pongboriboon; Keow Ngang Tang; Mark Wilson (Institute of Advanced Engineering and Science, 2020)
The main objective of this research was to develop and validate the quality of an assessment tool for evaluating the mathematical reading, analytical thinking, and mathematical writing skills of fourth-grade students. We randomly selected 222 fourth grade students across multiple schools of varying sizes to take the assessment. Multidimensional Random Coefficients Multinomial Item Response Model was applied to validate the quality of the developed assessment tool. A design-based research methodology was adopted to develop the assessment tool encompassing four phases as follows: 1) analyze how students solve mathematical problems; 2) develop the assessment tool; 3) validation of the tool; and 4) reflection. The results of this research indicate that the assessment tool consisting of 19 items and two dimensions is a reliable and valid metric to measure mathematical reading, mathematical writing and analytical ability of fourth graders. The Likelihood-Ratio test showed that the multidimensional model fits better in comparison to the unidimensional model. It can be concluded that each item is qualified to assess the students and relevant to the developed dimensional examination structure.